The Differences In The Company’s Financial Performance Before And After The Acquisition Period 2012-2015 (GEMA EKONOMI, 2022)
This research is seeks to analyze the differences in the company's financial performance before and after the acquisition of 2012-2015 by using financial ratios such as CR, QR, DER, DAR, TATO, FATO, NPM, ROE, EPS, and PER. There are 8 companies as a sample that were listed on Indonesia Stock Exchange (IDX). To analyze the data, the researcher used paired sample T-test. The result simultaneously showed that there was no significant difference before and after the acquisition. yet, partially the result shows that EPS in 1 year before and 2 years after acquisition; EPS and FATO in 2 years before and 2 years after acquisition; EPS and FATO in 2 years before and 3 years after acquisition; FATO and ROE in 3 years before and 2 years after acquisition; FATO, ROE and Financial Performance in 3 years before and 3 years after, had significant differences but there was no entire significant difference of financial ration within 3 years on trial. It means that the acquisition did not affect the companies. In other words, an economic motif could not be achieved.